Symbolic Capital of Power and Character Education Values in the Novel “Pasung Jiwa” by Okky Madasari - Kintan Amellia Agustin; Haerussaleh; Nuril Huda (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study examines the symbolic capital of power and the value of character education in the novel Pasung Jiwa by Okky Madasari. The source of data in this study is the novel Pasung Jiwa by Okky Madasari, while the data are in the form of phrases, words, or sentences that contain forms of symbolic capital of power and the value of character education. Data collection techniques used in the form of reading, library, and note-taking techniques, while data analysis techniques in the form of data reduction, data presentation, and conclusions. The findings obtained from this study consist of (1) forms of symbolic capital of power which are symbolized by position, image, social status, and authoritarian parenting to perpetuate their power; and (2) character education values, namely religious character values, honest character values, and hard work character values.